(untitled) (INNOVATIVE ECONOMY, 2020)
Sakhatskyi M.P., Zapsha H.M., Sakhatskyi M.M. MANAGEMENT OF DEVELOPMENT OF ECONOMIC POTENTIAL AT AGRICULTURAL ENTERPRISES AND FARMS Purpose. The aim of the article is to substantiate the theoretical and methodological foundations and development of practical recommendations for improving the management of economic potential development of agricultural enterprises and farms. Methodology of research. The methods of generalization, systematization, analysis, abstraction are used in the process of research to determine the directions of improving the management of development of agricultural enterprises and farms in terms of rationalization of their organizational structure of management and training and professional development of managers and marketers in accordance with the requirements of the present. Information base of scientific research is made by scientific works of domestic scientists-economists on the problem of improving the management of economic potential development of agricultural enterprises and farms. Findings. The objective nature of the need for continuous improvement of agricultural and farm development management is substantiated. It is established that the factors that cause the need to improve the management of the development of agricultural enterprises are: reduction of the number of farms, a decrease in the number of employees, a decrease in profit and profitability. It is substantiated that improvement of management of development of agricultural enterprises and farms implies rationalization of organizational structure of management by creation of marketing subdivision, according to which the adaptive function of bringing the production and market activity of the economic entity into conformity with dynamic changes of the environment is fixed. Training and selection of managers and marketers of agricultural enterprises and farms should include educational programs and advanced training in the acquisition of their professional competence in the constant adaptation of economic entities and their management structures and staff to the dynamic changes of the internal and external environment. Originality. Further substantiation of objective character of improvement of management of development of economic potential of agricultural enterprises and farms has been further developed, which, unlike others, includes rationalization of organizational structures of management and training of modern managers and marketers, whose professional competences are aimed at constant adaptation of economic entities to market changes. Practical value. The results of the study can be used to streamline organizational structures of management of agricultural enterprises and farms, as well as in training managers and marketers. Key words: management; potential; agricultural enterprises; farms; financial result; organizational structure of management; competence; adaptation; marketing.